Tìm x , biết :
a.(3x + 4)3 = (9x - 8)(3x2 -8)
b.(4x - 5)3 = (2x + 5)(16x2 - 25)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b) ta có \(\left(4x-5\right)^3-\left(2x+5\right)\left(16x^2-25\right)=0\)
\(\left(4x-5\right)^3-\left(2x+5\right)\left(4x+5\right)\left(4x-5\right)=0\)
\(\left(4x-5\right)\left[\left(4x-5\right)^2-\left(2x+5\right)\left(4x+5\right)\right]=0\)
\(\left(4x-5\right)\left(16x^2-40x+5^2-8x^2-10x-20x-5^2\right)=0\)
\(\left(4x-5\right)\left(8x^2-70x\right)=0\)
=> \(\orbr{\begin{cases}4x-5=0\\8x^2-70x=0\end{cases}=>\orbr{\begin{cases}4x=5\\x\left(8x-70\right)=0\end{cases}< =>}\orbr{\begin{cases}x=\frac{5}{4}\\\orbr{\begin{cases}x=0\\8x-70=0=>x=\frac{35}{4}\end{cases}}\end{cases}}}\) \(\orbr{\begin{cases}4x-5=0\\8x^2-70x=0\end{cases}< =>\orbr{\begin{cases}x=\frac{5}{4}\\x\left(8x-70\right)=0\end{cases}\orbr{\begin{cases}x=\frac{5}{4}\\\orbr{\begin{cases}x=0\\8x-70=0=>x=\frac{35}{4}\end{cases}}\end{cases}}}}\)
\(\orbr{\begin{cases}4x-5=0\\8x^2-70x=0\end{cases}=>\orbr{\begin{cases}x=\frac{5}{4}\\x\left(8x-70\right)=0\end{cases}}}\)
=> \(\orbr{\begin{cases}x=0\\x=\frac{35}{4}\end{cases}}\) Vậy \(\orbr{\begin{cases}x=\frac{5}{4}\\x=0\end{cases}}\) hoặc \(x=\frac{35}{4}\)
a)
<=> 3x - 3 + x - 2 = 2x - 2 - x + 1
<=> 3x + x - 2x + x = -2 + 1 + 3 + 2
<=> 3x = 4
<=> x = 4/3
Các câu sau làm tương tự
\(\left(3x-3\right)+\left(x-2\right)=\left(2x-2\right)-\left(x-1\right)\)
<=> \(3x-3+x-2=2x-2-x+1\)
<=> \(4x-5=x-1\)
<=> \(3x=4\)
<=> \(x=\frac{4}{3}\)
Vậy....
1.a) (4x - 6y)2 - (8xy - 5)2 = (4x - 6y - 8xy + 5)(4x - 6y + 8xy - 5)
b) 16x2 - 49y2 = (4x)2 - (7y)2 = (4x - 7y)(4x + 7y)
c) 36x2 + 60x + 25 = (6x)2 + 2.6x.5 + 52 = (6x + 5)2
d) (2x - y)(x - y) - (3y - 4x)2 + (y - 2x)(2y - 3x) = (y - 2x)(y - x) + (y - 2x)(2y - 3x) - (3y - 4x)2
= (y - 2x)[(y - x) + (2y - 3x)] - (3y - 4x)2 = (y - 2x)(3y - 4x) - (3y - 4x)2 = (3y - 4x)[(y - 2x) - (3y - 4x)] = 2(3y - 4x)(x - y)
2.M = (3x - 4)(9x2 - 12x + 16) + (6x - 8)2 = (3x - 4)[(3x)2 - 2.3x.4 + 42] + [2(3x - 4)]2 = (3x - 4)(3x - 4)2 + 4(3x - 4)2
= (3x - 4)2(3x - 4 + 4) = 3x(3x - 4)2
a)(x+2).(x+3)-(x-2).(x+5)=10
( x^2 +3x+2x+6)-(x^2 +5x-2x-10)=10
x^2 +3x+2x+6-x^2 -5x+2x+10-10=0
2x+6=0
2x=-6
x=-3
b: \(\dfrac{\left(x^2-1\right)\left(x^2+1\right)-2x\left(x^2-1\right)}{x^2-1}\)
\(=x^2-2x+1\)
\(=\left(x-1\right)^2\)
c: \(=\dfrac{5x^4-5x^3+14x^3-14x^2+12x^2-12x+8x-8}{x-1}\)
\(=5x^3+14x^2+12x+8\)
a) \(\left(3x-4\right)^3=\left(9x-8\right)\left(3x^2-8\right)\)
\(\Leftrightarrow27x^3+108x^2+144x+64=27x^3-72x-24x^2+64\)
\(\Leftrightarrow27x^3+108x^2+144x+64-27x^3+72x+24x^2-64=0\)
\(\Leftrightarrow132x^2+216x=0\)
\(\Leftrightarrow12x\left(11x+18\right)=0\)
\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\11x+18=0\end{array}\right.\)\(\Leftrightarrow\left[\begin{array}{nghiempt}x=0\\x=-\frac{18}{11}\end{array}\right.\)